(untitled) (Social Science Review, 2023)
It is widely known that women’s economic empowerment can lead to economic growth. Information communication technologies (ICTs) have been promoted as tools for national development. In this context, women have been promoted themselves as entrepreneurs through connecting more people by using ICT tools effectively. This paper mainly focuses on the role of ICT for women entrepreneurship development in Bangladesh. It also represents different social, cultural barriers women face in using ICTs in their business purposes. To make the study more effective questionnaire method was used. For this study 100 women have been selected from different online business pages and sent them the questionnaire. Among them 20 women entrepreneurs respond the questionnaire which included questions on role of ICT, training on ICT, mostly use of device, monthly income, availability of ICT institutions, access of ICT, barriers of using ICT and so on. It is argued in the study that women are becoming adapt themselves with technology especially in their business purpose and lead to contribute to the country’s economy. Lack of awareness, social, cultural structure are the major barriers to bring them as entrepreneurs and change their life. Social Science Review, Vol. 39(3), Dec 2022 Page 17-35